Characterizing hydroclimatic variability in tributaries of the Upper Colorado River Basin - WY 1911-2001 - Matter, Margaret A., author; Garcia, Luis A., advisor; Fontane, Darrell G., advisor (Colorado State University. Libraries, 2009)
Mountain snowpack is the main source of water in the semi-arid Colorado River Basin (CRB), and while the demands for water are increasing, competing and often conflicting, the supply is limited and has become increasingly variable over the 20th Century. Greater variability is believed to contribute to lower accuracy in water supply forecasts, plus greater variability violates the assumption of stationarity, a fundamental assumption of many methods used by water resources engineers in planning, design and management. Thus, it is essential to understand the underpinnings of hydroclimatic variability in order to effectively meet future water supply challenges. A new methodology was applied to characterize time series of temperature, precipitation, and streamflow (i.e., historic and reconstructed undepleted flows) according to the three climate regimes that occurred in CRB during the 20th Century. Results for two tributaries in the Upper CRB show that hydroclimatic variability is more deterministic than previously thought because it entails complementary temperature and precipitation patterns associated with wetter or drier conditions on climate regime and annual scales. Complementary temperature (T) and precipitation (P) patterns characterize climate regime type (e.g., cool/wet and warm/dry), and temperatures increase or decrease and precipitation changes magnitude and timing according to the type of climate regime Accompanying each climate regime type, are complementary T and P patterns on annual scales that are associated with upcoming precipitation and annual basin yield. Annual complementary T and P patterns: (a) establish by fall; (b) are detectable as early as September; (c) persist to early spring; (d) are related to the relative magnitude of upcoming precipitation and annual basin yield; (e) are unique to climate regime type; and (f) are specific to each river basin. Thus, while most of the water supply in the Upper CRB originates from winter snowpack, statistically significant indictors of relative magnitude of upcoming precipitation and snowmelt runoff are evident in the fall, well before appreciable snow accumulation. Since natural and anthropogenic external forcings, including solar variability, anthropogenic climate change, and modifications to land use, land cover and water use, influence the climate modes that shape climate regimes, the external forcings also influence the complementary temperature and precipitation patterns accompanying each climate regime. Consequently, although complementary temperature and precipitation patterns are similar for climate regimes of the same type (e.g., cool/wet climate regimes), they also differ and the differences may be associated with anticipated or observed effects of external forcings. In summary, this research shows that hydroclimatic variability during the 20th Century is more deterministic than previously thought, and includes: (a) a series of alternating patterns in temperature and precipitation corresponding with changes in climate regimes; and (b) effects of anthropogenic external forcings on the complementary temperature and precipitation patterns accompanying the climate regimes. Results of this research suggest alternative strategies to incorporate into existing water supply forecasting methods to improve forecast accuracy and increase lead time up to six months, from April 1 to October 1 of the previous year. Based on the relationships revealed by this research, the physical mechanisms behind the relationships may be determined and used to improve models for water supply forecasting and water management; develop long-range forecasts; and downscale climate models. In addition, the research results may also be used: (a) to improve application of or develop alternatives to engineering and hydrologic methods based on the assumption of stationarity; (b) in developing science-based adaptive management strategies for natural and cultural resource managers; and (c) in developing restoration, conservation and management plants for fish, wildlife, forest, and other natural resources.
Keywords: colorado river basin; hydroclimatic variability; land use change; tributaries; water supply; hydrologic sciences; civil engineering; environmental engineering; climate change; water resources management